2010
DOI: 10.3109/03639045.2010.489559
|View full text |Cite
|
Sign up to set email alerts
|

Production and characterization of testosterone undecanoate-loaded NLC for oral bioavailability enhancement

Abstract: This opens the perspective of administering a single dose of dose of TU in one oral dosage unit and simultaneously having a bioavailability less dependent on the fed state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…For instance, Muchow et al . observed that small sized NLCs (200 nm) showed higher AUC values in comparison to higher sized NLCs (600 nm) when administered orally to rats, this was attributed to their higher mucoadhesion capability in the body [36]. …”
Section: Fabrication Of Nlcsmentioning
confidence: 99%
“…For instance, Muchow et al . observed that small sized NLCs (200 nm) showed higher AUC values in comparison to higher sized NLCs (600 nm) when administered orally to rats, this was attributed to their higher mucoadhesion capability in the body [36]. …”
Section: Fabrication Of Nlcsmentioning
confidence: 99%
“…21 Recently, NLCs have been investigated to improve the oral bioavailability of poorly water-soluble drugs. [22][23][24][25][26] In this study, SM-loaded NLCs (SM-NLCs) were prepared by a high-pressure homogenization method and characterized for particle size, entrapment efficiency, morphology, in vitro lipolysis, and in vitro release. The preparative variables were optimized.…”
Section: Introductionmentioning
confidence: 99%
“…The terminal alkene of uC 11 reduces its hydrophobicity compared to the saturated C 11 salt, with a resultant increase in solubility and critical micelle concentration (CMC) (15,16). UA and its salts have been used as penetration enhancers in transdermal drug delivery (17,18), and there have been attempts to improve oral delivery of testosterone using a UA ester (19,20); however, the use of either UA and/or uC 11 specifically as intestinal permeation enhancers has never been investigated. uC 11 is a powder, more amenable to commercial-scale solid dose manufacturing than the acid form and was therefore more appropriate for the current oral drug delivery study.…”
Section: Introductionmentioning
confidence: 99%